Hyperimmunoglobulin E syndrome and multiple brain abscesses - Sahoo, Sushama; Ganguly, Tusti (Indian Journal of Child Health, 2014)
Hyperimmunoglobulin E (HyperIgE) syndrome is a rare primary immunodeficiency disease characterizedby recurrent skin and pulmonary infections and an elevated serum IgE level. We report a female neonatewith hyperIgE syndrome who presented with multiple brain abscesses and superficial cold abscesses causedby Staphylococcus aureus and also developed pneumonia later on. On follow-up, she developed pneumoniatwice and cold abscess once. She responded well to conservative management.